DAMPAK KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BPRS ATTAQWA: THE IMPACT OF LEADERSHIP AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT BPRS ATTAQWA - Alim, Muhammad Nurul; Oktaviani, Nurlita; Maulana, Irwan; Junaedi, Edy (Islamic Banking & Economic Law Studies (I-BEST), 2025)
This study aims to determine the influence of leadership style and work discipline on employee performance at PT BPRS Attaqwa. Employing a quantitative research method, the study involved all 30 employees of PT BPRS Attaqwa as a saturated sample. Data were collected using questionnaires and analyzed through hypothesis testing (t-test and F-test). The findings indicate that leadership style positively and significantly affects employee performance. Similarly, work discipline also has a positive and significant impact on employee performance. Furthermore, leadership style and work discipline simultaneously exert a positive and significant influence on employee performance. These results imply that management should prioritize both effective leadership development and the continuous enhancement of work discipline to optimize employee performance. A combined focus on both factors is crucial for achieving optimal outcomes in this sharia banking institution.